(untitled) (Mongolian Journal of Agricultural Sciences, 2023)
The study investigated the biochemical composition and enzyme activities of various radish and beet species, revealing significant variations across different parameters. Reducing sugars, crucial for blood sugar regulation and weight management, showed diverse levels among species, with higher concentrations observed in yellow turnip and white radish. Likewise, fiber content varied, with Raphanus sativus L. var. niger J. Kern exhibiting the highest fiber content. Moisture and mineral content also differed across species, with sugar beet displaying the highest mineral content. Regarding vitamin C content, our findings indicated lower levels compared to previous studies, suggesting potential influences of environmental conditions on vitamin accumulation. Flavonoid content, known for its antioxidant properties, was notably high in black radish compared to other species, highlighting the potential health benefits of flavonoid-rich varieties. Enzyme activities, including catalase, peroxidase, and polyphenol oxidase, varied among species, with white radish and beetroot exhibiting higher catalase activity. These findings highlight biochemical variations among radish and beet species, underscoring their potential health benefits and applications.